Exploring Pedagogical Grammar to Improve Communication Skills of Second-Semester University Students - Safriyani Novitri; Khulaifiyah, Khulaifiyah; Astuti, Missi Tri; Rizqiani, Diyah Ayu; Kurnia, Rima Maulani (UIR Press, 2026)
The purpose of this learning is to explore the application of the educational grammar. Engaging in the pedagogical grammar approach can help students communicate better. Student cognitive memories of the word strengthen their skill. A qualitative methodology was employed for data collection, utilizing observation as the principal tool for evaluating students' competencies. The research concept is based on training programs that motivate students to use English more often. As a result, English became a second language for most students more often in everyday life and in the classroom. The analysis also indicated learners seemed much better able to speak the language when they employed the pedagogical grammar approach. Researchers saw that they were more excited and sure of themselves when they spoke English in both planned and unplanned activities. In short, the pedagogical grammar approach made it easier for students to talk to each other. After receiving this kind of training, the students' eagerness and willingness to use English more frequently and with greater confidence demonstrate its effectiveness. Cognitive processes should involve how individuals perceive, think, and understand the world around them.